Advances in research on effects and mechanisms of ozone exposure on asthma and chronic obstructive pulmonary disease - Jiali WENG; Chenfei LI; Feng LI (环境与职业医学, 2023)
Ozone has become one of the major global environmental pollutants, and has attracted more and more attention in the field of air quality and public health. Ground-level ozone concentrations have been increasing in recent years, causing serious burden to the human respiratory system and social economy. Asthma and chronic obstructive pulmonary disease (COPD) are two common airway diseases. Ozone exposure can induce the occurrence, development and exacerbation of chronic airway diseases, short-term ozone exposure can induce non eosinophilic asthma, long-term ozone exposure can induce COPD, and ozone exposure can also induce acute attack of asthma and acute exacerbation of COPD. The effects are mainly that ozone exposure can mediate inflammatory response, oxidative stress, airway hyperresponsiveness, and DNA damage, and lead to decreased lung function, changes in microbial communities, and disruption of the air-blood barrier. This paper reviewed a series of epidemiological studies and animal experiments on asthma and COPD related to ozone exposure in recent years, and mainly generalized the effects of ozone exposure on airway diseases. Finally, this paper summarized the shortcomings of existing studies, providing a beneficial direction and ideas for further research on the hazards of ozone exposure on asthma and COPD and for exploring new intervention targets.